Menggali Nilai-Nilai Luhur Pada Tradisi Upacara Ngarot : Kajian Budaya Mengenai Nilai-Nilai Luhur Pada Tradisi Upacara Ngarot Di Desa Lelea Kabupaten Indramayau Provinsi Jawa Barat - Yunus Winoto (Fakultas Adab dan Humaniora UIN Raden Fatah, 2021)
This study aims to determine the noble values ​​contained in the implementation of the ngarot traditional ceremony in Lelea Village, Indtamayu Regency, West Java Province. The approach in research using a qualitative approach with the type of case study research. The data collection technique was carried out through observations, interviews and through literature study. Sources of data in the study include primary data sources derived from observations and interviews with resource persons consisting of young people, traditional leaders, village heads and Lelela village community leaders. The data analysis technique is carried out in three stages, namely the data reduction stage where the researcher collects and reduces the data, the data display stage, the researcher presents the data in the form of a narrative and description and the stage of drawing conclusions. Based on the research results, it is known that there are several values ​​that can be obtained from the implementation of this ngarot traditional ceremony, namely the spirit of mutual cooperation; exemplary symbols from community leaders for young people; enthusiasm to maintain the rice fields in Lelea Village as rice granaries in Indramayu Regency; the use of flowers on the crown or head as a symbol to maintain dignity and honor for girls or cuene as well as the meaning expressed in the mask dance movement which gives a message that human life does not escape death and will definitely end so that humans must always continue to work, do good according to with the age level in his life.